2014
DOI: 10.1007/s11517-014-1157-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of spinal cord stimulation profiles from intra- and extradural electrode arrangements by finite element modelling

Abstract: Spinal cord stimulation (SCS) currently relies on extradural electrode arrays that are separated from the spinal cord surface by a highly conducting layer of cerebrospinal fluid. It has recently been suggested that intradural placement of the electrodes in direct contact with the pial surface could greatly enhance the specificity and efficiency of stimulation. The present computational study aims at quantifying and comparing the electrical current distributions as well as the spatial recruitment profiles resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 46 publications
0
27
0
3
Order By: Relevance
“…The therapeutic window for stimulation parameters thus widens, whereas it is now relatively narrow for epidural stimulation [11]. With the ability to selectively activate a larger number of Aβ fibers, the net "dose" of current density delivered in a more focused way within the desired target zone in the dorsal columns will be higher, with greater potential for improved pain relief [14].…”
Section: Results Of Preliminary Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic window for stimulation parameters thus widens, whereas it is now relatively narrow for epidural stimulation [11]. With the ability to selectively activate a larger number of Aβ fibers, the net "dose" of current density delivered in a more focused way within the desired target zone in the dorsal columns will be higher, with greater potential for improved pain relief [14].…”
Section: Results Of Preliminary Testingmentioning
confidence: 99%
“…Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 6/28/15 2:32 AM Careful computational investigations have now confirmed that intradural SCS should indeed permit more selective activation of dorsal column axons without unwanted fiber activation, compared with epidural SCS [14]. We have also carried out studies of the biophysics underlying this concept, of the testing protocols, and fixation techniques used in in vivo experimentation, and of the histological evidence of safety with direct electrical stimulation of the spinal cord [5,6,9,12,13,21,23,24,29,33].…”
Section: New Device Conceptmentioning
confidence: 99%
“…In parallel with that, we are conducting finite element analyses of the current distributions that can be produced within the target tissues by intradural stimulation and comparing them with the existing epidural models. 34 Most recently, we have also undertaken a series of studies involving reciprocating translational movement of our spinal cord surrogate with the HSCMS mounted on it, to determine the ranges of motion available relative to the lead-loop's upper attachment point, before the rostral and caudal tips of the device begin to lift off the surrogate's surface.…”
Section: Discussionmentioning
confidence: 99%
“…Models of SCS have been continuously refined and applied from the early 80's through recent efforts 1,2,5,10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] (see Table 1). Development of models of increasing complexity offered mirrored general enhancements in numerical modeling techniques (finite element analysis), with proprietary efforts by numerous groups, each subject to multiple version iterations.…”
Section: Broad Impact Of An Open-source High-resolution Computationalmentioning
confidence: 99%